2017
DOI: 10.1111/tbj.12792
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Hypofractionated Radiotherapy, Toxicity and Outcome in Early Breast Cancer

Abstract: To compare adjuvant conventional radiotherapy (C-RT) to hypofractionated schedule (HF-RT) in early breast cancer. Between May 2012 and September 2015, 120 patients were included in the analysis. All patients underwent conservative surgery and adjuvant RT. RT was delivered in C-RT (50 Gy; 2 Gy/fr) or HF-RT (42.5 Gy; 2.66 Gy/fr), followed by a tumor bed boost (10 Gy; 2 Gy/fr). RT-induced toxicity was recorded and compared between groups. Toxicity results were graded according to the Common Terminology Criteria f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 14 publications
(22 reference statements)
2
23
0
Order By: Relevance
“…De Felice et al found that higher irradiated breast volume and conventional RT have a negative effect on acute skin toxicity. 18 Matrix metalloproteases (MMPs) are a family of enzymes that differ in their structure, substrate specificity, sequence homology, cellular localization and secretion. For this reason, they are divided into different subfamilies: collagenases, gelatinases, matrilysins, stromelysins, membrane type MMPs and others MMPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…De Felice et al found that higher irradiated breast volume and conventional RT have a negative effect on acute skin toxicity. 18 Matrix metalloproteases (MMPs) are a family of enzymes that differ in their structure, substrate specificity, sequence homology, cellular localization and secretion. For this reason, they are divided into different subfamilies: collagenases, gelatinases, matrilysins, stromelysins, membrane type MMPs and others MMPs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, RT can be combined with surgery and/or systemic therapy. 18 In BC, the most commonly used RT regimens are conventional RT (45)(46)(47)(48)(49)(50) Gy in fractions of 2 Gy) and hypofractionated RT (normally 42.5 Gy in fractions of 2.66 Gy). 19 The efficacy obtained with RT can vary according to the chosen RT regimen and to increased radioresistance in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is the most common cancer in women worldwide. Based on tumor and patient characteristics, treatment involves a multimodality approach which includes a combination of surgery with or without radiotherapy and/or systemic therapy [1].…”
Section: Introductionmentioning
confidence: 99%
“…This will result in reduced costs and waiting patient list and making treatment more acceptable for patients and hence decrease patient psychological morbidity associated with a long treatment course [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation